The Urgency of State Administration Attitude for Good Governance - Jejen Hendar; Efik Yusdiansyah; Neni Ruhaeni; Rusli K. Iskandar (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Good Governance is a fundamental concept in public Good Governance is a fundamental concept in public sector management that emphasizes the importance of transparency, integrity, responsibility, fairness, trust, balance, clarity, honesty, consistency, rule of law, vision, and mission in the public sector. In Indonesia, the government administration system is recognized as a crucial element in ensuring national progress and development. Thus, the concept of Good Governance is viewed as an important element in reforming the public sector and transforming it into a system that reflects accountability, responsibility, and transparency in its operations. To achieve the goals of Good Governance, it is essential to establish a strong and effective system of government administration. Such a system must prioritize the application of Good Governance principles in the planning, implementation, and accountability processes. The relationship between the attitudes of state administration and public service delivery is also critical in achieving Good Governance. The attitudes of state administration play a crucial role in shaping the foundation for Good Governance. It is important to note that Good Governance cannot be achieved solely through the implementation of policies and regulations.